The difficulties that secondary school teachers face in using electronic learning platforms in Yanbu Governorate, Kingdom of Saudi Arabia - Al-Rifai, Noof Mohammed; Al-Sisis, Areej Hamza (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the difficulties that secondary school teachers face in using electronic learning platforms in Yanbu Governorate, Kingdom of Saudi Arabia, and the extent to which these difficulties differ in light of some variables. 1686) male and female teachers, and to collect data, the questionnaire was designed as a tool for the study, so that the questionnaire was applied to an intentional sample of (320) from the study population. ) with a percentage of (67.6%), followed by the dimension of technical difficulties faced by teachers at electronic education platforms at a medium degree, where the arithmetic average reached (3.38), and finally came the dimension of the skill difficulties that teachers face in using electronic education platforms, and its content ranked last with an arithmetic average of ( 3.14 with a percentage of (62.8)%. The results also indicated that there were no statistically significant differences due to the variable (gender, level of technical expertise, number of Training courses (on the skill difficulties that teachers face in using e-learning platforms and their content, technical difficulties that teachers face when using e-learning platforms, and the results indicated that there are statistically significant differences due to the variable (level of technical expertise, number of training courses) about difficulties related to ease of use E-learning platforms and their perceived benefit.